The biological impacts of Indigenous residential school attendance on the next generation - Kat Chief Moon-Riley; Jennifer L. Copeland; Gerlinde A.S. Metz; Cheryl L. Currie (Elsevier, 2019)
We investigated the biological impacts of Indigenous residential school attendance on the adult children of survivors, operationalized through allostatic load (AL); and the extent to which intergenerational trauma, operationalized through adverse childhood experience (ACE) score, mediated this association. Data were collected in-person from a university-based sample of Indigenous adults (N = 90, mean age: 28 years) in a mid-sized city in western Canada between 2015 and 2016. Associations were analyzed in multinominal regression models, with terciled AL and ACE scores as outcomes. The cross-products of coefficients method was used to test mediation. Overall, 42.7% and 33.7% reported their mother and father had attended residential school; respectively. In an adjusted model, maternal, but not paternal, residential school attendance was a risk factor associated with a moderate increase in AL among her adult children. The strength of this association did not change when the analysis was limited to mothers who raised their children. Maternal and paternal residential school attendance were each associated with increased ACE score among adults raised by survivors. However, ACE score did not explain the association between maternal residential school attendance and offspring AL score in mediational analyses. The present findings suggest colonial residential school experiences may have become biologically embedded, passed to subsequent generations, and exhibited through the dysregulation of allostatic systems among the adult children of maternal residential school survivors. Maternal exposure to residential school influenced biological dysregulation among her adult children in ways that could not be further exacerbated by her children's exposure to ACEs. The Canadian Truth and Reconciliation Commission asked governments to acknowledge the impact of residential schools on the current state of Indigenous health. Our findings underline the importance of this call by demonstrating how the residential school experience may get under the skin to impact the health of the next generation. Keywords: Residential school, Indigenous, Allostatic load, ACEs, Intergenerational trauma